2020
DOI: 10.5798/dicletip.706097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of Monocyte / HDL Ratio In Routine Hemodialysis And Peritoneal Dialysis Patients

Abstract: Objective: Chronic kidney disease (CKD) is an inflammatory process. Serum proinflammatory cytokines are known to be ten times higher in patients with CKD when compared to normal population. Monocyte/High density lipoprotein (HDL) cholesterol ratio (MHR) have been shown to be a new marker of inflammation and claimed that, it may be used to predict cardiovascular events in patients with CKD. This cross-sectional study aimed to compare monocyte / HDL cholesterol ratio in patients treated with hemodialysis and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An increased count of pro-inflammatory monocytes and a reduced level of anti-inflammatory HDL cholesterol have been considered novel markers of inflammation. As a result of these studies, the monocyte to HDL cholesterol ratio (MHR) has emerged as a novel marker for determining endothelial injury, inflammation, and oxidative stress [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…An increased count of pro-inflammatory monocytes and a reduced level of anti-inflammatory HDL cholesterol have been considered novel markers of inflammation. As a result of these studies, the monocyte to HDL cholesterol ratio (MHR) has emerged as a novel marker for determining endothelial injury, inflammation, and oxidative stress [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MHR has become a useful marker of poor prognosis in a varius cardiovascular diseases [19][20][21] . Higher levels of monocytes secreting proinflammatory and prooxidant cytokines and lower HDL-C, which has an antiinflammatory and antioxidant effect, after all MHR indicates inflammation and oxidation in the body 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients hospitalized with acute edematous pancreatitis between 01.01.2021-31.12.2021 in Afyonkarahisar Health Sciences University Faculty of Medicine Hospital Internal Diseases Clinic were retrospectively scanned from the hospital electronic file system. Hospitalization Ranson score of these patients; age >70 years, white blood cell (WBC) >18000 mm 3 , glucose >220 mg/dL, lactate dehydrogenase (LDH) >400 U/L, aspartate aminotransferase (AST) >250 U/L parameters. Patients with a Ranson score below 3 were considered as mild pancreatitis and were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Monocyte/HDL is one of the new inflammation parameters frequently used in recent years [3]. In many previous studies, it can be a marker of inflammation and oxidative stress; it has been shown to be closely related to the presence and prognosis of some cardiovascular diseases [10,11].…”
Section: Univariate Analysismentioning
confidence: 99%
See 1 more Smart Citation